(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Which of the several theoretical models of intergenerational justice developed in the ethical and legal spheres has been implemented in climate litigation? In order to answer this question, this paper compares some of the main theoretical constructions put forward over the past decades on the subject of future generations, and then examines whether and how these have been transposed by the courts in their decisions. The thesis put forward is that, from a comparative perspective, two antithetical approaches oppose each other: an ecocentric view, centred on the protection of the collective rights of future generation, and an anthropocentric view, based on the future enjoyment of the individual freedoms of present generations.